Non-Halal Aspects on Company listed in the Jakarta Islamic Index - Muchlis, Mustakim (Hasanuddin Economics and Business Review, 2021)
Abstract. This study aims to measure the effect of non-halal transactions such as interest-based debt and non-halal income on firm value companies listed in the Jakarta Islamic Index. The sample used in this study were companies listed in Jakarta Islami Index 2015-2019. Data processing uses SPSS and results that interest-based debt and non-halal income partially and simultaneously have a negative relationship with firm value. This shows that Islamic values have become a consideration for investors in the ratification of the Islamic stock exchange in Indonesia.